Avaliação de queijos Colonial e Colonial Imbriago submetidos a diferentes tempos de produção e maturação - Pereira, Elisangela Borsoi (2014)
Two experiments were conducte, in order to identify the best time for production and maturation of Traditional Colonial and Imbriago Colonial cheese in the municipality of Pinhão - Paraná. Ten Holstein heifers, grazing on pasture and supplemented, individually provided 11 liters of milk in the morning. The total volume was clotted raw immediately after milking, at 32°C, followed traditional Colonial process. One hundred cheeses were produced in five different seasons, each one subjected to seven maturation times, where zero for production day, one, two, three, four, six and eight months of maturation. Samples were weighed in duplicate, measured for water activity (Aw), number of lactic acid bacteria (LAB), lipolytic and proteolytic mesophilic and presence of Listeria spp. Temperature and ambient relative humidity were recorded. All data were subjected to analysis of variance (ANOVA), applied Tukey test, at 5% significance and analyzed by Sisvar statistical program. In the first study, the parameters on the Traditional Colonial Cheese were evaluated from time zero to eighth months of maturation. The lineation was completely randomized, in a double factorial scheme, considering the production period as factor 1 and maturation time as factor 2. The second work evaluated the peeling treatment occurred in the third month, in times four, six and eight months of maturation. The lineation was in randomized blocks in a scheme of split plots, being block: production period; plot: maturation time; and subplot: peeling treatment. In the first work, for weight loss, there was no difference between the cheeses at the end of eight months. The loss was relevant until the second month of maturation, the process initial critical phase. To Aw, cheeses made in May and June remained with the highest concentrations, and the ones produced in November with the lowest values. To BAL, for all assessed cheeses there was significant increase in the first month, but the decrease occurred only for cheeses made in November and May, indicating that the process of acidification and subsequent maturation stabilization may have occurred with more efficiency in these months. As for lipolytic bacteria, cheeses made in May and June had the highest scores, probably due to lower temperatures. For proteolytic bacteria, there was an evident effect of the coldest times on the counts, especially until the second month of maturation. Comparing the peeling treatments, in the second study, there was no effect on weight loss, lipolytic and proteolytic mesophilic bacteria counting. Imbriago cheeses showed contents for Aw and lactic acid bacteria counts significantly higher than Traditional Colonial, starting only in the fourth month of maturation, which may be a consequence of the hydration occurring at the peeling treatment time. It can be concluded that cheeses produced in May can be indicated as the best period for production, both for the colonial as for the Imbriago. Regarding the peeling treatment, the probable rehydration does not represent a health risk